A study on dental referrals between general practitioners and dental specialists in San Juan, Metro-Manila - David, Ma. Paz S.
This research paper entilted, A study on dental referrals between general practitioners and dental specialists in San Juan, Metromanila, is an informative paper the attempts to provide fresh insights on dental referrals upon the senior class. This study aims to know if dental referrals is being practiced by a majority of general practitioners and dental specialists in San Juan, Metromanila. Also to know which field of dental discipline mostly referred, to know the problems commonly encountered during referrals. And to have an insight on the views of general practitioners and dental specialists on professional ethics during referrals. This study was conducted in San Juan, Metromanila having an approximately 95 dentists to serve 145,649 residents as of the year 1988. Questionnaires were personally handed-out and were collected a week after to all general practitioners and dental specialists whose clinics are located in San Juan, Metromanila. Results showed that majority of general practitioners and dental specialists practiced dental referrals, with orthodontics having the most referred dental discipline in San Juan area.